Ideal and distorted vortex lattice in bulk and film superconductors - Brandt, Ernst Helmut (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The solution of the linearized Ginzburg–Landau theory describing a periodic lattice of vortex lines in type-IIsuperconductors at large inductions and discovered first by Abrikosov, is generalized to nonperiodic vortex arrangements, e.g., to lattices with a vacancy surrounded by relaxing vortex lattice and to periodically distorted lattices that are needed in the nonlocal theory of elasticity of the vortex lattice. Generalizations to lower magnetic inductions and to three-dimensional arrangements of curved vortex lines are also given. It is shown how the periodicvortex lattice can be computed for bulk superconductors and for thick and thin films in a perpendicular field for all inductions B̅ and all Ginzburg–Landau parameters κ.